7(x+3y) -2(x-5y) Would the answer be: 7x +21y -2x +10y =5x +31y OR 7x +21y -2x -10y =5x +11y
J JohnRobbo New member Joined Mar 30, 2013 Messages 12 Apr 14, 2013 #1 7(x+3y) -2(x-5y) Would the answer be: 7x +21y -2x +10y =5x +31y OR 7x +21y -2x -10y =5x +11y
D Deleted member 4993 Guest Apr 14, 2013 #2 JohnRobbo said: 7(x+3y) -2(x-5y) Would the answer be: 7x +21y -2x +10y =5x +31y OR 7x +21y -2x -10y =5x +11y Click to expand... You don't tell us what you wanted to do with the expression Assuming that you wanted to expand and simplify - the first attempt is correct. 7(x+3y) -2(x-5y) = 7x +21y -2x +10y = 5x +31y
JohnRobbo said: 7(x+3y) -2(x-5y) Would the answer be: 7x +21y -2x +10y =5x +31y OR 7x +21y -2x -10y =5x +11y Click to expand... You don't tell us what you wanted to do with the expression Assuming that you wanted to expand and simplify - the first attempt is correct. 7(x+3y) -2(x-5y) = 7x +21y -2x +10y = 5x +31y
J JohnRobbo New member Joined Mar 30, 2013 Messages 12 Apr 14, 2013 #3 Subhotosh Khan said: You don't tell us what you wanted to do with the expression Assuming that you wanted to expand and simplify - the first attempt is correct. 7(x+3y) -2(x-5y) = 7x +21y -2x +10y = 5x +31y Click to expand... yes it was to expand and simplify thanks
Subhotosh Khan said: You don't tell us what you wanted to do with the expression Assuming that you wanted to expand and simplify - the first attempt is correct. 7(x+3y) -2(x-5y) = 7x +21y -2x +10y = 5x +31y Click to expand... yes it was to expand and simplify thanks